Artificial Intelligence is changing Health and eHealth care - Akshaya AVR; S., Vigneshwaran; Kumar C, Ram (EAI Endorsed Transactions on Smart Cities, 2022)
Artificial Intelligence (AI) will be used more and more in the healthcare industry as a result of the complexity and growth of data in the sector. Payers, care providers, and life sciences organisations currently use a variety of AI technologies. The main application categories include recommendations for diagnosis and treatment, patient engagement and adherence, and administrative tasks. Although there are many situations in which AI can execute healthcare duties just as well as or better than humans, implementation issues will keep the jobs of healthcare professionals from becoming extensively automated for a substantial amount of time. The use of AI in healthcare and ethical concerns are also highlighted.
Keywords: Artificial Intelligence; clinical decision support; electronic health record systems